An unexpected urinary bladder xanthoma: Case report - Martina Mandarano; Guido Bellezza; Giovanni Cochetti; Giulio Metro; Ettore Mearini; Rachele Del Sordo (临床与病理杂志, 2021)
In spite of the fact that xanthomas of the skin, tendons and mucosae are relatively common conditions, urinary bladder xanthoma is a rare benign lesion, only occasionally reported in literature. It usually appears as an exophytic mass into the bladder cavity, which often worries the clinicians, because it is considered as a neoplasm that need both an excision and follow-up. We herein describe the 32nd case, accidentally identified in a 63-year-old man with a right urinary bladder mass on follow-up abdominal ultrasound scan for a previous open pyeloplasty. He also referred mild obstructive lower urinary tract symptoms. Consequently, a cystoscopy with biopsies was performed and the subsequent histopathological examination was consistent with the diagnosis of urinary bladder xanthoma. Therefore, no additional therapeutics interventions were needed, and the patient currently presents nor symptoms, recurrences, or other pathologies. Although its rarity, it is important to correctly identify urinary bladder xanthoma, differentiating it from other pathological entities which present similar histopathological characteristics, but which sometimes could be associated with a patients’ dismal prognosis. Moreover, an accurate diagnosis of urinary bladder xanthoma can avoid both additional treatments and follow up, but also allows to recognize some potential detrimental pathologies which could be associated with it, such as either an altered lipid metabolism or urothelial neoplasms. Proper and prompt recognition and treatment of these last can notably improve patient’s outcome.